Bionomia e etologia do Mocis latipes (Guenee, 1852) (Lepidoptera-Noctuidae) - Silva, José Cordeiro da (1977)
Data are given on the post-embryonic development under experimental conditions, of Mocis latipes (Guenée, 1852) ,a highly polyphagous species, with marked preference for Gramineas. Data are also given on its ethology.